Business Model Canvas Training for Self-Development of Santri and Santriwati at Bahrul Ulum Islamic Boarding School, Jombang: Pelatihan Business Model Canvas Untuk Pengembangan Diri Santri dan Santriwati Pondok Pesantren Bahrul Ulum Jombang - Valentino Orlando Febrian; Raden J. Hadi Raharjo (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Pondok Pesantren Bahrul Ulum Jombang is one of the oldest boarding schools that has a long history of producing generations that are not only superior in religious knowledge, but also able to contribute to community development. In their role as part of the pesantren community, santri are not only active in the field of da'wah but also contribute to community-based economic development. One of them is by developing entrepreneurial potential through Business Model Canvas development training. This training was carried out for four weeks, including the introduction of the Business Model Canvas (BMC) concept, assistance in preparing business models, and evaluation through group presentations. The results showed a significant increase in santri's understanding and ability to design a business model based on the nine elements of BMC. The mentoring and coaching approach proved effective in creating a personalized, interactive, and applicable learning environment. This research provides a strategic contribution in empowering santri as agents of change who are competitive in the business world and becomes a replicable model for the development of community-based entrepreneurship.